Kin Recognition in Plants: Did We Learn Anything From Roots? - Biedrzycki, Meredith L.; Bais, Harsh P. (Frontiers in Ecology and Evolution, 2022)
Kin recognition, although manifesting through various traits such as changes in root or shoot growth, has been documented in several species of plants. Although identifying this phenomenon in plants has intrinsic value itself, understanding why plants recognize kin and how it might benefit them evolutionarily has been of recent interest. Here we synthesize studies regarding nutrient and resource allocation in regard to kin recognition as well as discuss how kin recognition is involved in multispecies interactions with an emphasis on how plant roots are involved in these processes. Future directions of this research are also explored.